Inconsistency of the Constitutional Court Regarding the Minimum Age Requirement for Presidential and Vice-Presidential Candidates: Inkonsistensi Mahkamah Konstitusi Terkait Syarat Minimal Usia Calon Presiden dan Wakil Presiden - Situmeang, Selvi Christina; Ardilafiza, Ardilafiza; Dinata, Ari Wirya (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
This paper discusses several Constitutional Court decisions concerning the minimum age requirements for presidential and vice-presidential candidates that were issued on the same day. In Constitutional Court Decisions Number 29/PUU-XXI/2023, Number 51/PUU-XXI/2023, and Number 55/PUUXXI/ 2023, the Court consistently rejected all petitions. However, later in the afternoon, through Constitutional Court Decision Number 90/PUU-XXI/2023, the Court changed its stance and partially granted the request. This paper aims to analyze the differences among these decisions and the Constitutional Court’s inconsistency when addressing decisions that substantially challenge the same article. This research employs a normative legal approach using primary, secondary, and tertiary legal materials. The findings of this study indicate discrepancies between the decisions, procedural irregularities, and drastic shifts in the judges’ perspectives. These factors have resulted in the Constitutional Court’s inconsistency in ruling on the issue of the minimum age requirements for the President and Vice President.